2019
DOI: 10.1002/jnr.24430
|View full text |Cite
|
Sign up to set email alerts
|

Exercise induces region‐specific remodeling of astrocyte morphology and reactive astrocyte gene expression patterns in male mice

Abstract: Astrocytes are essential mediators of many aspects of synaptic transmission and neuroplasticity. Exercise has been demonstrated to induce neuroplasticity and synaptic remodeling, such as through mediating neurorehabilitation in animal models of neurodegeneration. However, the effects of exercise on astrocytic function, and how such changes may be relevant to neuroplasticity remain unclear. Here, we show that exercise remodels astrocytes in an exercise-and region-dependent manner as measured by GFAP and SOX9 im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 54 publications
2
39
0
Order By: Relevance
“…Previous experimental work has shown that physical exercise was able to increase the levels of the astrocyte marker, GFAP, in the hippocampus [63] and induce changes in the astrocyte morphology, suggesting beneficial effects on neuronal activity and plasticity [63]. In a recent study, an increase in the number of astrocytic processes during the exercise protocol was observed in other brain areas, such as the prefrontal cortex, striatum, and entorhinal cortex of mice [64].…”
Section: Discussionmentioning
confidence: 92%
“…Previous experimental work has shown that physical exercise was able to increase the levels of the astrocyte marker, GFAP, in the hippocampus [63] and induce changes in the astrocyte morphology, suggesting beneficial effects on neuronal activity and plasticity [63]. In a recent study, an increase in the number of astrocytic processes during the exercise protocol was observed in other brain areas, such as the prefrontal cortex, striatum, and entorhinal cortex of mice [64].…”
Section: Discussionmentioning
confidence: 92%
“…The most commonly reported exercise-induced effects in astrocytes include morphological changes, together with elevation or suppression in the levels of glial fibrillary acidic protein (GFAP) [ 14 19 ] . The reported difference in GFAP levels may be explained partly by astrocyte heterogeneity and partly by differences in the type of exercise intervention.…”
Section: Introductionmentioning
confidence: 99%
“…All statistical tests were carried out and graphs made in Prism 8.3 (GraphPad, San Diego, CA) with statistical significance set at p < 0.05. No sample size calculations were performed prior to the start of the study but are based on previous publications from our lab (Halliday et al, 2019;Lundquist et al, 2019). All data included was normally distributed as assessed by Shapiro-Wilk normality testing, and no data points 10 were excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical Staining: Whole brains (fixed) were sliced in coronal sections (30 μm thickness) on a sliding freezing microtome (Leica CM1900, Leica Microsystems, Wetzlar, Germany) as previously described (Lundquist, Parizher, Petzinger, & Jakowec, 2019). Briefly, sections were washed in Tris- Immunocytochemical Staining: Primary astrocytes grown on PDL-coated coverslips were washed twice with ice-cold DPBS before being fixed with ice-cold 4% PFA-PBS (pH 7.2) for 10 minutes.…”
Section: Immunofluorescent Stainingmentioning
confidence: 99%
See 1 more Smart Citation